Tracing the Harmony between the Qur’an and Modern Scientific Discoveries through Al-Kindi’s Theory - Clara Wulandari; Ripki Nur Ilham; Bima Aulia Ramdhan; Muhamad Andi Septiadi (KEDJATI Journal of Islamic Civilization, 2025)
The perceived tension between religious revelation and modern scientific inquiry has often led to scepticism about the epistemic role of the Qur’an in contemporary knowledge development. This study aims to analyse the harmony between the Qur’an and modern science through the philosophical framework of Al-Kindi. Employing a mixed-methods approach that integrates qualitative and quantitative techniques, the study examines Qur’anic perspectives alongside scientific interpretations to assess their coherence. The findings indicate a consistent, complementary relationship between Qur’anic principles and scientific understanding, suggesting that both serve as mutually reinforcing sources of knowledge. The study demonstrates that the Qur’an and modern science share a harmonious epistemological orientation grounded in rational inquiry and the pursuit of truth. This research contributes to ongoing discussions in Islamic philosophy and science–religion studies by reaffirming the relevance of Qur’anic epistemology in contemporary scientific discourse.